Transcriptional signature of rapidly responding NK cells reveals S1P5 and CXCR4 as anti-tumor response disruptors - Marta Puig-Gámez; Martijn Van Attekum; Theodor Theis; Alec Dick; John E. Park (Scientific Reports)
Abstract Natural killer (NK) cells are prototypic cytotoxic innate lymphocytes that can kill target cells, such as tumor cells, in the absence of antigen-restriction. Peripheral NK cells exhibit a high degree of heterogeneity. Here, we set out to broadly assess intrinsic modulators of NK cell degranulation in an unbiased manner. We stimulated human primary blood-borne NK cells pre-treated with different cytokine regimens with the HCT116 human colon cancer cell line and used detection of lysosome-associated membrane glycoprotein 1 (LAMP1) as an identifier of rapid NK cell degranulation. RNA sequencing of FACS-sorted LAMP1hi NK cells showed CXCR4 and S1PR5 were top down-regulated genes. Using compounds that modulate activity of CXCR4 and S1P receptor family members S1P1 and S1P5, we confirmed they play an important immunosuppressive role in NK cell cytotoxicity. Mechanistically, engagement of CXCR4 and S1P1/5 receptors triggered phosphorylation of p42 and Ca2+ influx. CXCR4 activation promoted S1P5 upregulation and vice versa, and joint activation of both receptors amplified the defect NK cell degranulation. Intriguingly, in tumor samples the expression of both receptors and the synthesis of their ligands themselves appear to be coordinately regulated. Together, these data suggest that specifically and simultaneously targeting CXCR4 and S1P5 activity in the tumor microenvironment (TME) could be a beneficial strategy to unleash full cytotoxic potential of cytotoxic NK effector cells in the tumor.